Utilization of Municipal Solid Waste Compost in Reclamation of Saline-sodic Soil Irrigated with Poor Quality Water - Arvind Kumar Rai, Rajender Kumar Yadav and Dinesh Kumar Sharma, Parul Sundha*, Nirmalendu Basak (Journal of the Indian Society of Soil Science, 2018)
Salinity and sodicity are the major stresses in soils of arid and semi-arid regions. These regions often facerainfall shortage and groundwater contains excess salts with variable sodium adsorption ratio (SAR).Therefore, a laboratory experiment was conducted to investigate the impact of municipal solid wastecompost (MSWC) in reclamation of saline-sodic soil with pH, electrical conductivity (EC) and exchangeablesodium per cent of 10.7, 3.09 dS m-1 and 70.3, respectively. Soil with gypsum (25 and 50% of gypsumrequirement, GR) and its combination with 10 and 20 t ha-1 of farmyard manure (FYM), MSWC of Karnal(KC) and Delhi (DC) were incubated at 60% field capacity. After 30 days of incubation, a soil columnleachingexperiment was carried out with treated and control soil. Columns were sequentially leached up toten pore volumes using water of SAR 5 and 15 with constant electrolyte concentration (60 me L-1). Nature,amount and independent integration of amendments had positive influence on lowering of soil pH and EC.The GR25DC (20 t ha-1) treated soil showed maximum decrease for both soil pH and EC irrespective ofSAR of water. Further, soil reclamation efficiency (based on losses of cation mass) increased with applicationof organic amendment rates (20 t ha-1) in conjunction with GR25 compared to non amended soil/ GR25 +lower doses of organic amendment. Quality and purity of agricultural grade gypsum is issue, thereforeGR25 and 20 t ha-1 MSWC can be advocated for reducing alkalinity and salinity stress of soil under use ofpoor quality water.